1215 Japanese encephalitis epidemic in northeast india: 45 cases. (1st December 2017) - McNaughton, Harry; Singh, Ashita; Khan, Siraj
Abstract : Background: Japanese encephalitis (JE) is endemic in large areas of south-east Asia. Epidemic JE in regions where JE is endemic tends to affect children rather than adults. There are few reports of epidemic JE in a previously unaffected region. We report our experience of a first-ever outbreak of JE in Sonitpur District, Assam, India with 45 laboratory-confirmed cases over a 6 week period at a single hospital. Method: All patients were assessed by two physicians, one of whom was a neurologist, in a 100-bed mission hospital. Where possible, CT head scan, blood (including acute and convalescent specimens for JE antibody titres) and CSF specimens were obtained. All JE specimens were tested at the ICMR laboratory in Dibrugarh, Assam. Results: Over a 6 week period there were 45 cases of JE confirmed on the basis of CSF or blood specimens. Mean age was 36 years (range 4–80). Ten/45 (22%) died and a further 20/45 (44%) had significant residual deficits. Focal neurological signs (40%) and seizures (25%) were common. CT scans were normal or suggested raised ICP. Short cases will be highlighted. Conclusion: This is a unique series of JE cases from a first-ever outbreak with careful clinical, radiological and laboratory assessment.